A simple theoretical framework for the analysis of liability dollarization - Heymann, Daniel (2004)
This paper presents a simple model of debt contracts in order to analyze the conditions under which domestic residents would choose to denominate debts in "dollars". In the model, borrowers are producers of non-traded goods, and subject to shocks on prices. The real exchange rate varies in response to real shocks. There is a domestic unit of account; prices in terms of that unit can be shocked by a (presumably policy-induced) disturbance. Debt obligations can be denominated in either traded goods (dollarized contracts) or local currency. When real and nominal shocks are possitively correlated, dollarized contracts tend to be preferable to (non-contingent) nominal contracts when nominal shocks are large and real shocks are small.